Development of high-performance sensor based on NiO/SnO2 heterostructures to study sensing properties towards various reducing gases. (9th July 2020) - Din, Salah Ud; Haq, Mahmood Ul; Sajid, Muhammad; Khatoon, Rabia; Chen, Xuehua; Li, Li; Zhang, Manjun; Zhu, Liping
Abstract: In this work, we report the spontaneous formation of NiO nanoparticles-decorated onto smooth SnO2 nanofibers, which is an inexpensive and scalable method for yielding a high composite surface area via a simple two-step synthesis process based on electrospinning and the hydrothermal method. A Nickel Oxide proton-conducting electrolyte is deposited homogeneously over a large surface area in a transparent solution, mixed and decorated onto Tin dioxide nanofibers, as evidenced by cross sectional imaging of the electrospun nanofibers. The composite based on nanoparticle-decorated fibers enlarges the surface area of the exposed electrolyte, which fundamentally improves the overall gas sensing performance. The crystal structure, morphology, and physio-chemical surface state of the NiO/SnO2 -based specimen are comprehensively examined using XRD, SEM, TEM, HRTEM, EDX, and photoelectron (XPS) spectroscopy. The composite based on NiO/SnO2 nanoparticle-decorated fibers exhibits an optimistic mesoporous nature with a huge specific area, which is key for superior gas sensors. The result reveals that NiO/SnO2 nanoparticle-decorated fibers with an average size of 180–260 nm in diameter, where the average length of fibers was about 1.5 μ m. The composite-based heterojunction of NiO/SnO2 nanoparticle-decorated fibers enhances the adsorption of oxygen molecules, which show fast response, good selectivity and quick recovery speed against ethanol gas at an optimal temperature of about 160 °C. The maximum sensitivity response of the sensor-based composite NiO/SnO2 nanoparticle-decorated fibers was 23.87 in respect of 100 ppm ethanol gas at a low temperature of 160 °C; this is approximately about 7.2 times superior to that of pure SnO2 nanofibers. The superior gas sensing capabilities of a composite based on NiO/SnO2 nanoparticle-decorated fibers may be attributable to the enhanced catalytic effect of the small sized NiO nanoparticles on smooth SnO2 nanofibers, together with the p/n heterojunction effects between NiO and SnO2 heterostructures.